G25(P) Drug induced short qt interval with use of anti-epileptic medications. (25th October 2020) - Choopa, S; Sesham, R; Nair, P
Abstract : Introduction: Although drug induced long QT intervals is known to have proarrhythmogenic effect, the same is not known about drug induced short QT intervals. Drug induced short QT syndrome is a rare occurrence and have mainly been reported with the use of anti epileptic medications. Proarrhythmic effects of drug induced QT shortening has only been shown with digitalis. The clinical relevance of drug induced QT shortening is currently unclear. Case Report: We report a case of drug induced QT shortening in a 15 year old boy being treated for Juvenile Myoclonic epilepsy. He was initially being treated with Sodium Valproate with later addition of levetiracetam. He started having complaints of intermittent palpitations and occasional dizziness. He was otherwise well with no family history of sudden deaths etc. His examination and echocardiography were normal. His ECG showed sinus rhythm with a QT interval of 340 milliseconds. His previous ECG 6 months ago had shown a QT interval of 330 milliseconds. An ECG done 3 years ago at diagnosis had shown a normal QT interval of 400 ms. He had subsequent multiple ambulatory monitoring and exercise stress tests which were also normal. He is under ongoing follow up with the cardiac team and his anti-epileptic medications have been continued. Discussion: Drug induced short QT interval is a rare phenomenon and have been mainly seen with use of some antiepileptics, digitalis & promethazine. Although there have been case reports of QT prolongation with use of levetiracetam, we could not find any reports of QT shortening. There were few reports of QT shortening when sodium valproate was used as a co-medication. In this case we are not sure if it is the valproate on its own or the addition of levetiracetam which caused the QT shortening. However based on no evidence of proarrhythmogenic effect with drug induced QT shortening, we agreed to continue his anti epileptic medications while closely monitoring him. More evidence base and research is needed to throw light on management of patients with drug induced short QT-intervals.